PERBEDAAN SENAM OTAK DAN SENAM POCOPOCO MENINGKATKAN FUNGSI EKSEKUTIF LANSIA STUDI EKSPERIMENTAL DI PUSAT SANTUNAN KELUARGA - Yuliana Yosephine,* Rr Josephine Retno Widayanti,* Yuda Turana* (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION THE ELDERLY HAVE THE RISK OF EXPERIENCING EXECUTIVE DYSFUNCTION DUE TO STRUCTURAL AND FUNCTIONAL CHANGES IN NEURONS AND SYNAPSES IN THE PREFRONTAL CORTEX ASSOCIATED WITH AGING THE BRAIN GYM AND POCOPOCO GYMNASTICS CAN MAINTAIN AND IMPROVE EXECUTIVE FUNCTION SO THAT PRODUCTIVITY AND QUALITY OF LIFE OF THE ELDERLY REMAIN OPTIMAL